Healthcare professionals' views on psychological support for children and families affected by skin conditions in the UK: A qualitative study - Olivia Hughes; Katherine H. Shelton; Andrew R. Thompson (Wiley, 2024)
Abstract Background Skin conditions can have a psychological impact on a child and their caregivers, however, support is not equally distributed between geographical regions in the United Kingdom (UK). Objectives This study aimed to investigate the experience of National Health Service (NHS) healthcare professionals (HCPs) of addressing the psychological needs of children with skin conditions and their families, and gain expert opinion as to how services need to further develop. Design HCPs were recruited to a qualitative study with an advert posted on social media. Methods Fifteen HCPs took part in interviews, including dermatologists (n = 4), dermatology nurse consultants/specialists (n = 4), clinical psychologists (n = 4), liaison psychiatrists (n = 2), and a children's psychological well‐being practitioner (n = 1). Results Thematic analysis revealed children often presented with anxiety, depression, self‐harm and suicidal ideation. The impact on caregivers was equally profound. There were differences in service provision across the UK and all HCPs recognised the urgent need for psychological support to be integrated into standard care. Participants described how a range of interventions are typically required including cognitive behavioural therapy (CBT), and systemic approaches, as well as mindfulness/third‐wave approaches. Barriers to the delivery of psychological services were associated with a lack of funding and training opportunities for core and specialist staff alike. However, in some instances, participants had overcome these challenges to be able to deliver unique services. Conclusions There exist several barriers to providing paediatric psychological interventions, and many locations across the UK remain vulnerable as a result of continuing lack of national guidelines for the provision of psychological services.